Distinct Community-Wide Responses to Forecasted Climate Change in Afrotropical Forests - Núñez, Chase L.; Poulsen, John R.; White, Lee J. T.; Medjibe, Vincent; Clark, James S. (Frontiers in Ecology and Evolution, 2022)
More refined knowledge of how tropical forests respond to changes in the abiotic environment is necessary to mitigate climate change, maintain biodiversity, and preserve ecosystem services. To evaluate the unique response of diverse Afrotropical forest communities to disturbances in the abiotic environment, we employ country-wide tree species inventories, remotely sensed climate data, and future climate predictions collected from 104 1-ha plots in the central African country of Gabon. We predict a 3 - 8% decrease in Afrotropical forest species richness by the end of the century, in contrast to the 30 - 50% loss of plant diversity predicted to occur with equivalent warming in the Neotropics. This work reveals that community forecasts are not generalizable across regions, and more representative studies are needed in understudied diverse biomes. This study serves as an important counterpoint to work done in the Neotropics by providing contrasting predictions for Afrotropical forests with substantially different ecological, evolutionary, and anthropogenic histories.